2022
DOI: 10.2478/hukin-2022-0054
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Oxygen Saturation Breakpoints Reflect Ventilatory Thresholds in Both Cycling and Running

Abstract: Pulmonary gas exchange analysis was compared to changes in muscle oxygen saturation as measured by near-infrared spectroscopy. First, ventilatory thresholds determined by common gas exchange analysis and breakpoints in muscle oxygen saturation were assessed for agreement during exercise with increasing intensity. Secondly, the relationship between muscle oxygen saturation as a surrogate for local oxygen extraction and peak oxygen uptake was assessed. In order to lend robustness to future NIRS testing on a broa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 31 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…Most studies with NIRS sensors have traditionally measured only one body side without clear reasoning [ 23 , 24 ]. Even when the same muscles are measured bilaterally, only one side is reported [ 38 ]. The additional aim of the present study was to evaluate the homogeneity of DeSmO 2 kinetics of the same region of contralateral VL muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies with NIRS sensors have traditionally measured only one body side without clear reasoning [ 23 , 24 ]. Even when the same muscles are measured bilaterally, only one side is reported [ 38 ]. The additional aim of the present study was to evaluate the homogeneity of DeSmO 2 kinetics of the same region of contralateral VL muscles.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies showed good correlations (r = 0.63) between gas exchange and SmO 2 data at the first threshold in cycling during step tests (van der Zwaard et al 2016). However, the results of the first threshold were not clearly defined in the study by Feldmann et al (2022), since both first thresholds are not correlated. The oxygen consumption increase during the first lactate threshold remains linear (Binder et al 2008) which may explain the difficulty for SmO 2 data to determine this point.…”
Section: Discussionmentioning
confidence: 80%
“…NIRS is a non-invasive technology and in some cases portable technology, which has been used in different sports (Perrey and Ferrari 2018), from team sports such as rugby (Jones et al 2013) to endurance sports such as testing athletes in cycling or running (Feldmann et al 2022). This technology detects the heme compound of hemoglobin, myoglobin and cytochrome oxidase, so as to calculate muscle oxygen saturation (SmO 2 ) using the main absorbing chromophores found in skeletal muscle (Barstow 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with a previous study using a maximal cycle-ergometer ramp test with 25 cyclists ( Racinais et al, 2014 ). However, other studies using incremental tests in cycling or running have observed correlations between one or both ventilatory thresholds and SmO 2 ( Austin et al, 2005 ; Fontana et al, 2015 ; van der Zwaard et al, 2016 ; Feldmann et al, 2022 ), which may be due to different NIRS devices used or certain differences in the protocol used, as graded incremental test with a lower speed increase (0.8 km/h each 3 min) than in our study ( Austin et al, 2005 ) or a 30 s stages test with speed increase of 0.5 km/h until to exhaustion ( Feldmann et al, 2022 ). In addition to this, it should be noted that in our study, a 30-s break was used between stages during the test.…”
Section: Discussionmentioning
confidence: 93%
“…During incremental exercises, the behavior of the SmO 2 variable has four phases: i) an initial increase, ii) a linear or exponential decrease below the resting baseline values iii) leveling off when the participant reaches maximal volitional fatigue during this incremental test, being these results the lowest and below the resting baseline values and, and iv) an increase over baseline values during the first minutes of recovery ( Bhambhani, 2004 ). There has been some controversy surrounding the use of NIRS devices during some incremental running or cycling tests, as some studies have shown correlations between ventilatory thresholds and SmO 2 breakpoints ( Austin et al, 2005 ; Feldmann et al, 2022 ), the first ventilatory threshold and SmO 2 breakpoint ( van der Zwaard et al, 2016 ), the second ventilatory threshold and SmO 2 breakpoint ( Fontana et al, 2015 ) or no clear correlations between ventilatory thresholds and SmO 2 breakpoints ( Racinais et al, 2014 ). For training monitoring purposes, NIRS is currently considered more useful than HR for monitoring running intensity in hilly terrain ( Born et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%